Diet in the Management of Functional Dyspepsia: Controversial and Unresolved Issues - A. A. Sheptulin; S. S. Kardasheva; A. A. Kurbatova (Российский журнал гастроэнтерологии, гепатологии, колопроктологии, 2023)
Аim: to analyze publications devoted to the study of the role of food in the occurrence of functional dyspepsia (FD), as well as the possibilities of using dietary nutrition in its treatment.Key findings. Many studies have shown that spicy food, food with a high content of saturated fats, coffee, carbonated drinks can lead to symptoms of FD. Intolerance to certain foods (in particular, wheat) may be associated with their ability to act as allergens. A number of studies have noted that elimination diets (a diet with a low content of FODMAP products and a gluten-free diet) reduce the severity of dyspeptic disorders, however, there is no convincing evidence of the effectiveness of these diets.Conclusion. The role of nutrition in the occurrence of FD and the possibility of using various diets in its treatment have not been sufficiently studied and require further research.